SIMULATION OF THE PROCESS OF FILLING WITH A VISCOUS LIQUID THE CAVITY OF THE PRESS-FORM FOR MOLDING OF SHOE PARTS - SYNYUK, OLEG; POLISHCHUK, OLEH; KUNTSOV, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article considers the determination of the optimal structural and technological parameters of injection molding, which are necessary to simulate the process of filling the mold cavity with a viscous liquid, which involves the construction of a numerical model of the flow of a viscous liquid in the mold cavity. The simulated process of the movement of a viscous liquid in the mold cavity using the finite element method. The implementation of the finite element method in the presented form leads to a symmetrical system of linear algebraic equations relative to the unknown nodal values of the velocity and pressure vector components. The use of the Moldex3D software complex made it possible to visualize the process of filling the cavity of the mold during the manufacture of the sole. The complex includes tools that provide automatic discretization of the initial area into triangular elements, formation of the matrix of finite elements taking into account the boundary conditions and solving the system of linear equations. By varying the location of the inlets and their diameters (that is, the initial values of the melt velocities in each inlet), it is possible to achieve the optimal location of the joining lines (places where the polymer solution flows are welded). Thus, simulating the process of filling the mold cavity with PVC material through the four inlet holes, it is possible to observe the process of formation of joints.The proposed mathematical model of the flow of a viscous liquid in the cavity of the mold and the method of its implementation using the Moldex3D software complex will allow determining the optimal design of the molds and the technological modes of the process of filling them with polymer material.
Keywords: mold; polymer melt; injection molding; model; finite element method; Moldex3D software complex